Crassula tanzae (Crassulaceae subfam. Crassuloideae), a new aquatic species in Crassula sect. Helophytum from the Drakensberg Mountain Centre, southern Africa - Crouch, Neil R.; Smith, Gideon F. (Phytotaxa, 2026)
A new aquatic species, Crassula tanzae (Crassulaceae subfam. Crassuloideae), is described from high altitude tarns and pans in the south-central Maloti-Drakensberg of South Africa and neighbouring Lesotho, to which region it is restricted. This new taxon is allied to C. natans, from which it is readily separable on a combination of vegetative and reproductive characters. A key diagnostic character of C. tanzae is its substantially swollen and short-internoded basal stem portion, with nodes along this stem section conspicuously constricted, and adjacent internodes bulging. The typification of the name C. natans is corrected.